Implementation of SAKTI Related to Internal Control of State Property Management at the Ministry of Foreign Affairs - Khasanah, Uswatun; Siswantoro, Dodik (E-Jurnal Akuntansi; Vol 35 No 4 (2025), 2025)
Management State Property at the Ministry of Foreign Affairs according to BPK is still less orderly and lack of internal control over fixed assets. With the application of SAKTI to record fixed assets, the purpose of this research is to find out the application of SAKTI in supporting the achievement of internal control in BMN management, and propose solutions to improve the shortcomings that still occur. This research uses a case study method with a qualitative approach. The data processed are the results of documentation studies, interviews and observations, then evaluated using PP 60 of 2008 concerning SPIP. The research findings show that the interconnection of SIMKEU with SAKTI contributes to improving internal control in BMN Management. Keywords: SAKTI; Management State Property; Internal Control; PP 60 year 2008; Fixed Assets